Conversion of ethanol in dynamic plasma-liquid system - Yukhymenko, V.V.; Verovchuk, M.O.; Olshewskii, S.; Chernyak, V.Ya.; Zrazhevskij, V.A.; Demchina, V.P.; Kudryavzev, V.S.; Shchedrin, A.I.; Levko, D.S.; Naumov, V.V. (Вопросы атомной науки и техники, 2009)
Experimental and theoretical research of the process of low-temperature transformations of mixture ethanol/water in
nonequilibrium plasma of the electric discharge in gas channel with fluid wall was carrying out. The gas channel in
liquids was created by two counter airstreams in liquids and vapor of the liquids. The gas chromatography and massspectrometric
techniques for investigation of stable gas-phase conversion products were used. The power inputs on
conversion of mixture in synthesis – gas were measured. The values of efficiency, coefficient of energy transformation,
specific energy requirement of system were calculated. Experimental results indicate the possibility and efficiency of
plasmachemical conversions of ethanol in syntheses-gas in such plasma-liquid system of the atmospheric pressure. Проводилось експериментальне та теоретичне дослідження процесів низькотемпературного перетворення
суміші етанол/вода в нерівноважній плазмі електричного розряду в газовому каналі з рідкою стінкою. Газовий
канал в рідині створювався двома зустрічними потоками повітря в рідині та парах рідини. Для дослідження
стабільних газо-фазних продуктів конверсії використовувались газова хроматографія та мас-спектрометрична
методика. Вимірювались енерговитрати на конверсію суміші в синтез газ. Обраховувались ефективність,
коефіцієнт трансформації енергії та питоме споживання енергії системи. Результати експериментів показали
можливість та ефективність плазмохімічної конверсії етанолу в синтез-газ в такій плазмово-рідинній системі
атмосферного тиску. Проводилось экспериментальное и теоретическое исследование процессов низкотемпературного
превращения смеси этанол/вода в неравновесной плазме электрического разряда в газовом канале с жидкой
стенкой. Газовый канал в жидкости создавался двумя встречными потоками воздуха в жидкости и парах
жидкости. Для исследования стабильных газо-фазных продуктов конверсии использовались газовая
хроматография и масс-спектрометрическая методика. Измерялись энергозатраты на конверсию смеси в синтез-
газ. Рассчитывались эффективность, коэффициент трансформации энергии и удельное потребление энергии
системы. Результаты экспериментов показали возможность и эффективность плазмохимической конверсии
этанола в синтез-газ в такой плазменно-жидкостной системе атмосферного давления.